2019
DOI: 10.1111/1541-4337.12457
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Bioavailability, and Mechanism of Emerging Activities of Ile‐Pro‐Pro and Val‐Pro‐Pro

Abstract: Ile‐Pro‐Pro and Val‐Pro‐Pro are two most well‐known food‐derived bioactive peptides, initially identified as inhibitors of angiotensin I‐converting enzyme (ACE) from a sample of sour milk. These two peptides were identified in fermented and enzymatic hydrolyzed cow and non‐cow (that is, goat, sheep, buffalo, yak, camel, mare, and donkey) milk, as well as sourdough prepared from wheat, rye, and malt. Similar to other bioactive peptides, bioavailability of these peptides is low (about 0.1%), reaching picomolar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 160 publications
(255 reference statements)
0
29
0
Order By: Relevance
“…Among the anti-hypertensive peptides found in FDFs, the lactotripeptides, VPP and IPP, gained great attention in recent years thanks to their increasingly frequent commercial use in hypotensive milk-drinks production. Indeed, numerous in vivo studies reported a blood pressure reduction in mildly hypertensive patients [23,51,75,76]. These lactotripeptides were initially detected in a sample of Japanese sour milk fermented by Lactobacillus helveticus and Saccharomyces cerevisiae and characterized for their ACE-inhibitory (ACE-i) activity and hypotensive effect in spontaneously hypertensive rats [52,77].…”
Section: Anti-hypertensive Peptides Identified In Commercial Fdfsmentioning
confidence: 99%
“…Among the anti-hypertensive peptides found in FDFs, the lactotripeptides, VPP and IPP, gained great attention in recent years thanks to their increasingly frequent commercial use in hypotensive milk-drinks production. Indeed, numerous in vivo studies reported a blood pressure reduction in mildly hypertensive patients [23,51,75,76]. These lactotripeptides were initially detected in a sample of Japanese sour milk fermented by Lactobacillus helveticus and Saccharomyces cerevisiae and characterized for their ACE-inhibitory (ACE-i) activity and hypotensive effect in spontaneously hypertensive rats [52,77].…”
Section: Anti-hypertensive Peptides Identified In Commercial Fdfsmentioning
confidence: 99%
“…The prominent examples from milk‐ and milk product‐derived ACE‐I peptides are VPP and IPP, which have received comprehensive review recently (Li et al., 2019). VPP and IPP were found to be degradation resistant and were able to exert ACE inhibition in aorta (Li et al., 2019). The IC 50 values of VPP (5 µM) and IPP (9 µM) are much higher than that of captopril (0.007 µM) (Li et al., 2019).…”
Section: Structure–activity Relationship Of Bpsmentioning
confidence: 99%
“…VPP and IPP were found to be degradation resistant and were able to exert ACE inhibition in aorta (Li et al., 2019). The IC 50 values of VPP (5 µM) and IPP (9 µM) are much higher than that of captopril (0.007 µM) (Li et al., 2019). By observation, both peptides fulfilled the structure–activity requirement of branched hydrophobic amino acid (valine and isoleucine) at the N‐terminus and the presence of aromatic hydrophobic amino acid (proline) at the C‐terminus.…”
Section: Structure–activity Relationship Of Bpsmentioning
confidence: 99%
“…Along with the above two pathways, the JAK-STAT pathway is also important for inflammatory response and can regulate hematopoietic cell development and inflammatory cytokines. Phosphorylation of JAK and STATs can form the dimer translocated to the nucleus [ 38 ]. BAPs can attenuate inflammation by inhibiting phosphorylation of JAK and STATs.…”
Section: Pathways Involved In the Inhibition Of Chronic Intestinalmentioning
confidence: 99%